The CMS Beam Halo Monitor electronics. (12th February 2016) - Tosi, N.; Dabrowski, A.E.; Fabbri, F.; Grassi, T.; Hughes, E.; Mans, J.; Montanari, A.; Orfanelli, S.; Rusack, R.; Torromeo, G.; Stickland, D.P.; Stifter, K.
Abstract: The CMS Beam Halo Monitor has been successfully installed in the CMS cavern in LHC Long Shutdown 1 for measuring the machine induced background for LHC Run II. The system is based on 40 detector units composed of synthetic quartz Cherenkov radiators coupled to fast photomultiplier tubes (PMTs). The readout electronics chain uses many components developed for the Phase 1 upgrade to the CMS Hadronic Calorimeter electronics, with dedicated firmware and readout adapted to the beam monitoring requirements. The PMT signal is digitized by a charge integrating ASIC (QIE10), providing both the signal rise time, with few nanosecond resolution, and the charge integrated over one bunch crossing. The backend electronics uses microTCA technology and receives data via a high-speed 5 Gbps asynchronous link. It records histograms with sub-bunch crossing timing resolution and is read out via IPbus using the newly designed CMS data acquisition for non-event based data. The data is processed in real time and published to CMS and the LHC, providing online feedback on the beam quality. A dedicated calibration monitoring system has been designed to generate short triggered pulses of light to monitor the efficiency of the system. The electronics has been in operation since the first LHC beams of Run II and has served as the first demonstration of the new QIE10, Microsemi Igloo2 FPGA and high-speed 5 Gbps link with LHC data.